Algebraic expression for extra degree added to hypercube interconnection network in case of multiple edge-faults - Karci, A (Ieee Computer Soc, 2001)
Researchers used more than one method for implementing algorithms on faulty hypercube interconnection networks. Some of them modified the structures of hypercube and the others did not modify the structure of hypercube and they implemented their operations on faulty hypercube. Modifying structure of hypercube requires adding extra degrees to each nodes and this called reconfiguration of hypercube. I improved an algebraic expression for added extra degrees to hypercube to make it non-faulty hypercube.
8th International Conference on Parallel and Distributed Systems (ICPADS 2001) -- JUN 26-29, 2001 -- KYONGJU CITY, SOUTH KOREA
Keywords: hypercubes; edge-fault tolerance; reconfigurations